"Saccidananda": A Christian Approach to Advaitic Experience - A Thannipara (Journal of Dharma, 1976)
Any keen and sincere mind can observe a slow but steady pro- gress in the process, of the meeting and understanding of the two great spiritual worlds of Hinduism and Christianity. In the beginning it was one of mutual confrontation and' rejection rather than that of tolerance and openness towards each other. In the next stage we see some sort of mere 'shaking of hands' which simply remained on the superficial plane. We see this mutual relationship gradually reach- ing the intellectual stage giving rise to a number of comparative studies. Now every sincere 'Seeker of truth' is well aware of the fact that the real meeting of the world's two richest religious heri- tages cannot remain on merely intellectual or comparative level but has to go deep down to the level of mind and heart, truth and spirit. In this book Swami Abhishiktananda tries to convince us that this meeting can take place most effectively only at the deepest level of authentic religious experience, i.e., the advaitic experience of the Self in Hinduism and Trinitarian experience in Christianity. He says: "It would seem as if India, moved by the Spirit, invites the Christian to seek the mystery of God, Creator and Saviour, no longer outside or alongside himself, but in the profoundest depths of his own heart" (p. 13)